Fabrication and characterization of sunflower protein isolate nanoparticles, and their potential for encapsulation and sustainable release of curcumin. (1st September 2021) - Mehryar, Laleh; Esmaiili, Mohsen; Zeynali, Fariba; Imani, Mehdi; Sadeghi, Rohollah
Highlights: Sunflower protein isolate (SnPI) nanoparticles were fabricated and characterized. Ethanol formed the most uniform and spherical SnPI nanoparticles. SnPI nanoparticles successfully encapsulated curcumin (up to 95%). A burst release followed by sustainable curcumin release was observed. Abstract: In this research, first, the effects of two desolvating agents (ethanol and methanol) at three temperature values (4, 25, and 50 °C) on the fabrication of sunflower protein isolate (SnPI) nanoparticles were studied using a desolvation method. Second, the ability of the nanoparticles to encapsulate curcumin was investigated. Results showed that ethanol led to smaller nanoparticles compared to methanol as the desolvating agent at 4 and 50 °C. However, at 25 °C, ethanol formed the most uniform nanoparticles with the lowest polydispersity index (0.188 ± 0.091) and particle size of 174.64 ± 30.61 nm. The encapsulation efficiency was in the range of 39.1 to 95.4% according to the fabrication condition and curcumin-to-protein mass ratio. A biphasic trend of curcumin release from nanoparticles was observed; in which, over 50% of curcumin was released from the curcumin-loaded nanoparticles in the first 2 h, which is attributed to the burst effect of the protein matrix.